2020
DOI: 10.1021/acsami.0c14300
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Skeleton–Heterostructure Composites Based on Chrome Shavings for Enhanced Electromagnetic Interference Shielding

Abstract: Renewable bio-based electromagnetic interference (EMI) shielding materials receive increasing attention undoubtedly. However, there is still a challenge to use raw biomass materials to construct a significant structure through an effortless and environmental route for EMI shielding applications. Herein, for the first time, we demonstrated a hybrid composite of multi-walled carbon nanotube/polypyrrole/chrome-tanned collagen fiber (MWCNT/PPy/CF), which utilized waste chrome shavings as a matrix. X-ray photoelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…Studies have shown that when people are exposed to electromagnetic radiation for a long time, the risk of diseases such as cancer, heart disease, skin problems, headaches and other mild or acute diseases will increase. Therefore, the design and development of lightweight, economical and efficient EMI shielding materials are imperative to address the problems of electromagnetic pollution [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that when people are exposed to electromagnetic radiation for a long time, the risk of diseases such as cancer, heart disease, skin problems, headaches and other mild or acute diseases will increase. Therefore, the design and development of lightweight, economical and efficient EMI shielding materials are imperative to address the problems of electromagnetic pollution [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these two composites are all reflection-dominated due to the R values exceeding 0.8. 43 Apparently, the UPC 15 composite has the highest R coefficient due to the integral structures of the CCB–polymer hybrid network. Then, the T , R , and A of the UPC composites as a function of CCB content are presented in Figure S4b–d .…”
Section: Resultsmentioning
confidence: 98%
“…Comparing with pure Ti 3 C 2 T x (Figure S3b,c), it is obvious to see the wrinkled Ti 3 C 2 T x covering the polymer matrix and forming a multilayer structure. As in the case of other composites loaded with conductive fillers, 23–25 the Ti 3 C 2 T x flakes are interconnected and randomly distributed in the composite, which promotes the formation of a continuous conductive network to achieve the desired EMI SE.…”
Section: Resultsmentioning
confidence: 99%